Stir-baked Xanthii fructus ameliorates adjuvant arthritis by regulating gut microbiota, short-chain fatty acids and metabolites - Cui, Xinyuan; Ding, Zhaoqi; Ji, Yujie; Liu, Jiale; Chang, Zenghui; Zhang, Junshuo; Wang, Xinyi; Liu, Kai; Liu, Yuanyuan (Frontiers in Microbiology, 2025)
IntroductionRheumatoid arthritis (RA) is a common and widespread autoimmune disease whose incidence is increasing. Stir-baked Xanthii fructus (XF) is used to treat RA in clinic. However, it’s in vivo efficacy and mechanistic pathways remain unclear. This study aimed to explored XF’s therapeutic effects and its mechanisms by comprehensive serum metabolomics and gut microbiota analysis.MethodsThe components in XF were identified using the UPLC-MS technique. A rat model of adjuvant arthritis was established using complete Freund’s adjuvant to evaluate the efficacy of XF. The in vivo mechanisms were explored through microbiome, short-chain fatty acid (SCFAs), and metabolomics analysis.ResultsIn total, 27 components were identified in XF. The treatment effectively suppressed inflammatory factors and alleviated pannus and cartilage damage. In addition, this article revealed a substantial remodeling of the gut microbiota composition, characterized by a reduced abundance of pro-inflammatory bacteria, increased populations of immunomodulatory bacteria and restored levels of SCFAs. Serum metabolomic profiling identified 17 arthritis-associated metabolites, primarily involved in glycerophospholipid metabolism and bile acid biosynthesis. Then, a strong correlation was found between gut microbiota and serum metabolites, indicating that XF exerts its therapeutic effects through immunomodulation, energy homeostasis regulation, and redox balance maintenance via the gut-joint axis.DiscussionThis study provides new insights for further research into the targeted therapy of XF to ameliorate adjuvant arthritis.